The development of the world trade and strengthening of protectionism in the world economy in the 1980-90-s - Matouk, Ali Emhmed M. (Marketing & Menedzsment, 2019)
A sign of recession is the declining foreign trade. One might be surprised that when there is industrial over-production, foreign trade declines. There is a tendency for foreign trade to become "one way" traffic with much more exports than imports. Consequently the trade partner who can not increase its exports becomes short of foreign currency, and has to decrease imports from the country, which wants to export at any cost. In this way, declining imports of a given country limits the exports of this country.